Нематеріальні активи як об’єкт обліку і звітності - Плекан, М. В. (Видавництво Львівської політехніки, 2014)
Розкрито значущість нематеріально-економічних ресурсів у функціонуванні підприємства постіндустріального типу. Розглянуто зміст та економічну природу нематеріальних активів як об’єкта системи бухгалтерського обліку і фінансової (корпоративної) звітності. Проаналізовано потенціал бухгалтерської методології для відображення об’єктів нематеріальних активів та їх формалізованої репрезентації у фінансовій звітності. Запропоновано окремі підходи до забезпечення формалізованих методик оцінювання нематеріальних активів підприємства, їх відображення у публічній фінансовій звітності. Reveals the importance of intangible resources and economic operation of the business postindustrial type. Proved that the rational management of intangible assets should be based on complete and accurate information about their availability and use, ie formalized characterization of all intangible objects formed in the accounting system. The content and economic nature of intangibles as the object of the accounting and financial (corporate) reporting. Consider the content and conceptual and methodological basis of accounting for intangible assets and regulations regarding their display in public financial statements. The results of the critical analysis of the existing standardization accounting for intangible assets, regulations for their display system statements. It is proved that accounting ill cope with certain types of intangible objects, especially those that are internally generated by the company. Systematized scientists suggested approaches to improving the methods of valuation of intangible assets for the purposes of display in the accounting system. The existing potential accounting methodology to reflect intangible assets and their formal representation in the financial statements. A separate approaches to formal methods of evaluating intangible assets, they appear in public financial statements.
Intangible assets as a subject of accounting and reporting
Keywords: нематеріальні активи; інтелектуальний капітал; система бухгалтерського обліку; фінансова звітність; звіт про інтелектуальний капітал; оцінка; аналіз; показники; intangible assets; intellectual capital; accounting system; financial statements; a report on intellectual capital; evaluation; analysis; indicators